A binding deficit: value-directed remembering for item-specific vs. associative information - DeLozier, Sarah J., author; Rhodes, Matthew G., advisor; Davalos, Deana, committee member; Folkestad, James, committee member; Cleary, Anne, committee member (Colorado State University. Libraries, 2018)
In a series of four experiments I examined whether value enhanced memory for item-specific or associative information. Value indicated the importance of an item at study (i.e., 1 point = low importance, 12 points = high importance), with memory typically being enhanced for high-value information (e.g., Castel, 2008). Utilizing the feature-conjunction paradigm, in which recognition errors for conjunction lures provide a means of examining whether value-enhanced recognition is a result of recollection or familiarity, the Pilot Experiment revealed through increased conjunction errors that value enhanced memory only for item-specific information. In Experiment 1 participants were permitted to self-pace their study and made confidence learning judgments (CLJs) after each recognition judgment. Learners spent more time studying higher-valued words yet demonstrated a similar pattern of increased conjunction errors by value. In Experiment 2, participants were instructed to use either rote repetition or interactive imagery for all words at study. Under these controlled study strategy conditions, conjunction errors were similar across values. In Experiment 3, I examined the influence of value on feature lures. When both feature lures and conjunction lures were presented at test, learners' susceptibility to lures was similar across values, yet learners correctly recognized more high-value old words. Results indicated that both encoding processes and item-based familiarity may contribute to a deficit in binding components of high-value words. These findings are discussed in terms of the negative effects of value on memory for associative information.
Keywords: binding; memory; self-regulated learning; feature-conjunction; associative recognition; motivation